Stretchable Transparent Polyelectrolyte Elastomers for All‐Solid Tunable Lenses of Excellent Stability Based on Electro–Mechano–Optical Coupling. Issue 3 (30th October 2022) - Zhong, Hao; Xue, Qiqi; Li, Jiameng; He, Yunfeng; Xie, Yuxin; Yang, Canhui
Abstract: Lenses are ubiquitously used for imaging. Compared with conventional lenses containing rigid translating components driven by mechanical motors, nonmechanical tunable lenses have been drawing attention owing to their advantages in compactness, lightweight, low power consumption, and fast response. Herein, inspired by the accommodation mechanism of the human eye, an all‐solid electromechanically tunable lens driven by a dielectric elastomer actuator is presented. A soft, stretchable, transparent, and ionically conductive polyelectrolyte elastomer, poly(3‐acrylamidopropyl)trimethylammonium chloride, is synthesized and used as the electrodes, one of which is plano‐convex and the other planar. A mold‐free procedure is elaborated to eliminate the contamination by molding and for facile fabrication. Subject to voltage, the resulting tunable lens achieves a relative change of focal length of ≈46.4%, superior to that of the human eye. The electro–mechano–optical coupling of the lens is modeled and the theoretical predictions agree well with the experimental results. Moreover, the tunable lens responds fast, operates stably in the ambient and desiccated environment, maintains performances over 1000 cycles, and exhibits a shelf‐life longer than 12 weeks. The polyelectrolyte elastomer‐based all‐solid tunable lens promises a potential solution for lightweight, compact, and durable imaging systems. Abstract : An all‐solid electromechanically tunable lens is fabricated based on soft, stretchable, transparent, and ionically conductive polyelectrolyte elastomers, which simultaneously function as electrode and optical lens. A relative change of focal length of ≈46.4%, exceeding that of the human eye, is achieved. The lens responds fast, operates stably in ambient and desiccated environments, over 1000 cycles, and over 12 weeks.